Tunable and Selective Conversion of 5-HMF to 2,5-Furandimethanol and 2,5-Dimethylfuran over Copper-Doped Porous Metal Oxides - Kumalaputri, Angela J.; Bottari, Giovanni; Erne, Petra M.; Heeres, Hero J.; Barta, Katalin (ChemSusChem, 2014)
Tunable and selective hydrogenation of the platform chemical 5‐hydroxymethylfurfural into valuable C6 building blocks and liquid fuel additives is achieved with copper‐doped porous metal oxides in ethanol. A new catalyst composition with improved hydrogenation/hydrogenolysis activity is obtained by introducing small amounts of ruthenium dopant into the previously reported Cu0.59Mg2.34Al1.00 structure. At a mild reaction temperature (100 °C), 2,5‐furandimethanol is obtained with excellent selectivity up to >99 %. Higher reaction temperatures (220 °C) favor selective deoxygenation to 2,5‐dimethylfuran and minor product 2,5‐dimethyltetrahydrofuran with a combined yield as high as 81 %. Notably, these high product yields are maintained at a substrate concentration up to 10 wt % and a low catalyst loading. The influence of different alcohol solvents on product selectivity is explored. Furthermore, reaction intermediates formed at different reaction temperatures are identified. The composition of these product mixtures provides mechanistic insight into the nature of the reduction pathways that influence product selectivity. The catalysts are characterized by elemental analysis, TEM, and BET techniques before and after the reaction. Catalyst recycling experiments are conducted in batch and in a continuous‐flow setup. With a little help from Ru: Selective and tunable hydrogenation of 5‐hydroxymethylfurfural (HMF) with earth‐abundant, copper‐based porous metal oxides (Cu‐PMOs) is achieved. Addition of a small amount of ruthenium dopant enhances the combined selectivity to 2,5‐dimethylfuran (DMF) and 2,5‐dimethyltetrahydrofuran (DMTHF) under optimized conditions.